2007
DOI: 10.1080/08856250701649989
|View full text |Cite
|
Sign up to set email alerts
|

The influence of teaching experience and professional development on Greek teachers’ attitudes towards inclusion

Abstract: On the assumption that the successful implementation of any inclusive policy is largely dependent on educators being positive about it, a survey was undertaken into the attitudes of Greek teachers toward inclusion. The 155 respondents were general education primary teachers drawn from one region of Northern Greece, with a proportion deliberately selected from schools identified as actively implementing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
232
6
45

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 332 publications
(315 citation statements)
references
References 32 publications
32
232
6
45
Order By: Relevance
“…The remaining participants, however, were all united in their assessment that in order for the mainstream classroom to be an effective learning environment, teachers of students with ASD have to be allocated considerable support. This viewpoint is well documented in the existing body of ASD literature (see Avramidis & Kalyva, 2007;McGregor & Campbell, 2001).…”
Section: Had One [Student] That Gave Me Cuddles But I Have To Keepmentioning
confidence: 77%
See 2 more Smart Citations
“…The remaining participants, however, were all united in their assessment that in order for the mainstream classroom to be an effective learning environment, teachers of students with ASD have to be allocated considerable support. This viewpoint is well documented in the existing body of ASD literature (see Avramidis & Kalyva, 2007;McGregor & Campbell, 2001).…”
Section: Had One [Student] That Gave Me Cuddles But I Have To Keepmentioning
confidence: 77%
“…While undoubtedly the extent of teachers' difficult experiences do relate to the severity of their students' needs (Avramidis & Kalyva, 2007;McGregor & Campbell, 2001), the present study has identified a number of specific teacher challenges and support issues which pertain specifically to the mainstreaming of students with ASD within the primary school setting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Teachers' attitudes toward inclusion have been found to be influenced by the nature of a learners' disability (Avramidis & Kalyva, 2007;Scruggs & Mastropieri, 1996), potentially because learners with more severe and multiple disabilities have more complex learning needs, require more significant adaptations to the curricula, and one-on-one instructional time. Research has found, for instance, that teachers rated learners with severe intellectual disabilities, autism, and sensory impairments the most challenging to include within a mainstream classroom (Avramidis & Kalyva).…”
Section: South African Teachers' Attitudes 5 Learner-level Factorsmentioning
confidence: 99%
“…elle prévient aussi les écarts de conduite et la présence de comportements perturbateurs (evertson & Weinstein, 2006 ;Kauffman, Mostert, trent, & Pullen, 2006 ;Myers & Pianta, 2008). néanmoins, des études démontrent que la gestion de classe s'avère très difficile pour une majorité d'enseignants (Brouwers & tomic, 2000 ;Martin, nault, & loof, 1994), surtout lorsque ceux-ci doivent intervenir auprès d'élèves présentant des difficultés comportementales (avramidis & Kalyva, 2007 ;Goodman & Burton, 2010 ;Helfin & Bullock, 1999 ;Jeffrey & sun, 2006). Plusieurs échelles mesurant le seP des enseignants ont été dévelop-pées au cours des trente dernières années (avanzi et al, 2013 ;dellinger, Bobbett, olivier, & ellett, 2008).…”
Section: Introductionunclassified